2015
DOI: 10.1103/physrevc.91.015809
|View full text |Cite
|
Sign up to set email alerts
|

Pairing properties and specific heat of the inner crust of a neutron star

Abstract: I investigate the pairing properties at finite temperature of the Wigner-Seitz cells in the inner crust of a neutron star obtained with the recent Brussels-Montreal Skyrme functional BSk21. In particular I analyze the phenomena of persistence and reentrance of pairing correlations and their impact on the specific heat in the low-density region of the inner crust.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 55 publications
(114 reference statements)
1
25
0
Order By: Relevance
“…It was shown that the transition temperature of the superfluid gas is correctly recovered, but the peak is still sharper than in the full HFB calculation. Moreover, in the full calculation a second peak at higher temperature can appear in the outer part of the inner crust, depending on the energy functional [5,9]. This peak corresponds to the temperature at which the whole system becomes non-superfluid, due to the pairing effect in the surface of the cluster.…”
Section: Computation Of the Total Energymentioning
confidence: 96%
See 1 more Smart Citation
“…It was shown that the transition temperature of the superfluid gas is correctly recovered, but the peak is still sharper than in the full HFB calculation. Moreover, in the full calculation a second peak at higher temperature can appear in the outer part of the inner crust, depending on the energy functional [5,9]. This peak corresponds to the temperature at which the whole system becomes non-superfluid, due to the pairing effect in the surface of the cluster.…”
Section: Computation Of the Total Energymentioning
confidence: 96%
“…This decomposition of the Wigner-Seitz cell between cluster and gas, accounting for the excluded volume effect, was tried in the recent HFB analysis of Ref. [9]. It was shown that the transition temperature of the superfluid gas is correctly recovered, but the peak is still sharper than in the full HFB calculation.…”
Section: Computation Of the Total Energymentioning
confidence: 99%
“…A semiclassical method that includes shell effects -namely the extended Thomas-Fermi plus Strutinsky integral method -was applied to assess the role of proton pairing [335]. It was found that pairing acts to smooth out the proton shell effects, without significantly changing the energetically favored value of Z, which was found to be close to 40. At the microscopic level, the Hartree-Fock-Bogolyubov theory [336] has been applied extensively in the past decade to determine the composition and pairing of crustal matter in neutron stars, as well as its specific heat, using the WS approximation; see [261,[337][338][339][340][341][342] and references therein for the earlier work. The key features related to the behavior of the relative magnitude of the gaps in the continuum and the cluster bound state discussed above are reproduced in this case as well.…”
Section: Pairing Patterns In Neutron Starsmentioning
confidence: 99%
“…The set of these minima describes a path in the (Z, ρ b , R W S ) configuration space, hence defining in details the evolution of the structure of the inner crust of neutron stars from its outmost to its inmost regions. In the current article, we limit ourselves to the zero-temperature case, but the formalism can be extended to include the non-zero temperature case [41,42]. We investigate a region of the baryonic density that spans 0.0004 fm −3 ≤ ρ b ≤ 0.02 fm −3 .…”
Section: The Methodsmentioning
confidence: 99%
“…In the limit of vanishing pairing gap ∆ q nn ′ lj → 0 one retrieves the usual Hartree-Fock equations on a basis. More details on the solutions of these equations can be found in Refs [55,[60][61][62].…”
Section: A Nuclear Energy Enucmentioning
confidence: 99%